Automatic Ground Surface Reconstruction from mobile laser systems for driving simulation engines. (March 2017) - Craciun, Daniela; Deschaud, Jean-Emmanuel; Goulette, Francois
Driving simulation engines represent a cost effective solution for vehicle development, being employed for performing feasibility studies and tests failure and for assessing new functionalities. Nevertheless, they require geometrically accurate and realistic three-dimensional (3D) models in order to allow driver training. This paper presents the Automatic Ground Surface Reconstruction method, a framework that exploits 3D data acquired by Mobile Laser Scanning systems. They are particularly attractive due to their fast acquisition at the terrestrial level. Nevertheless, such a mobile acquisition introduces several constraints for the existing 3D surface reconstruction algorithms. The proposed surface modeling framework produces a regular surface and recovers sharp depth features within a scalable and detail-preserving framework. Experimental results on real data acquired in urban environments allow us to conclude on the effectiveness of the proposed method.